2020
DOI: 10.1097/hcr.0000000000000531
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of NT-Pro Brain Natriuretic Peptide During Exercise Recovery in Ischemic Heart Failure of Reduced, Midrange, and Preserved Ejection Fraction

Abstract: Background: Ischemic heart disease is a leading cause of heart failure (HF), which continues to carry a high mortality despite considerable improvements in diagnosis and treatment. N-terminal-pro-B-type natriuretic peptide (NT-pro-BNP) measured at rest is a recognized diagnostic and prognostic marker of HF of reduced ejection fraction (HFrEF); however, its value in patients with HF of midranged/preserved ejection fraction (HFmrEF/HFpEF) is not well established. We examined the prognostic value of NT-pro-BNP du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…Previous studies have showed that E/eʹ and NT-proBNP are predictive of death or HF re-hospitalizations in acute HFpEF or ischemic HF patients. [28][29][30] Consistent with these results, our findings showed that the RVarterial uncoupling group had significantly elevated E/e′, NT-proBNP, and IVC compared with the RV-arterial coupling group. Elevated E/eʹ and NT-proBNP were associated with the primary endpoint and recurrent HF hospitalizations.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have showed that E/eʹ and NT-proBNP are predictive of death or HF re-hospitalizations in acute HFpEF or ischemic HF patients. [28][29][30] Consistent with these results, our findings showed that the RVarterial uncoupling group had significantly elevated E/e′, NT-proBNP, and IVC compared with the RV-arterial coupling group. Elevated E/eʹ and NT-proBNP were associated with the primary endpoint and recurrent HF hospitalizations.…”
Section: Discussionsupporting
confidence: 88%
“…NT-proBNP has the advantages of long half-life and high stability, and its clinical significance is equivalent to BNP (brain natriuretic peptide). [20][21][22][23][24][25] The level of blood BNP reflects the heart function of the patient. BNP .400 pg/mL is However, in this study, the postoperative NT-proBNP level was significantly lower in the test group than in the control group, demonstrating that the cardiac function of the patients was better in the test group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…NT-proBNP has the advantages of long half-life and high stability, and its clinical significance is equivalent to BNP (brain natriuretic peptide). 20–25 The level of blood BNP reflects the heart function of the patient. BNP >400 pg/mL is regarded as heart failure in the European Heart Association guidelines.…”
Section: Discussionmentioning
confidence: 99%